Child marriage and family reunification: an analysis under the European Convention on Human Rights of the Dutch Forced Marriage Prevention Act. Issue 2 (June 2017) - Wijffelman, Anne
The Dutch Forced Marriage Prevention Act aims to prevent family reunification of so-called child brides with their husbands in the territory of the Netherlands by no longer recognizing child marriages concluded abroad as legal marriages. Although it can be argued that the Netherlands has an obligation not to recognise a child marriage concluded abroad, it is disputable whether the Forced Marriage Prevention Act is in line with other human rights obligations. This article analyses whether the rights of child brides are violated under Articles 8 and 3 of the European Convention on Human Rights, if their family reunification application is denied. Although the minor spouse is most likely residing outside the territory of the Netherlands, a family reunification procedure brings her nevertheless within its jurisdiction, and as such within the sphere of the European Convention on Human Rights.